Polyphase rifting and break-up of the central Mozambique margin. (February 2019) - Senkans, A.; Leroy, S.; d'Acremont, E.; Castilla, R.; Despinois, F.
Abstract: The break-up of the Gondwana supercontinent resulted in the formation of the Central Mozambique passive margin as Africa and Antarctica were separated during the mid-Jurassic period. Although plate kinematics during the oceanic spreading phase are well constrained, the initial fit of Africa and Antarctica, their earliest relative movements and margin architectures remain active areas of interest. This study uses high quality multi-channel seismic reflection profiles to identify the major crustal domains in the Angoche and Beira regions of the Central Mozambique margin. Our results show that the Central Mozambique passive margin is characterised by intense but localised magmatic activity, evidenced by the existence of seaward dipping reflectors (SDRs) in the Angoche region, and magmatic sills and volcanoclastic material marking the Beira High. The Angoche and Beira regions possess faulted upper-continental crusts, with possible exhumation of lower crustal material forming an extended ocean-continent transition (OCT). The Beira High segment reveals an offshore continental fragment, which is overlain by a faulted pre-rift sedimentary unit likely to belong to the Karoo Group. The combination of our seismic interpretation with existing geophysical and geological data has allowed us to propose a break-up model which supports the idea that the Central Mozambique margin was affected by polyphase rifting. The Beira High basement is formed by a strike-slip deformation along a proposed lithospheric weakness - the Lurio-Pebane shear zone. Northwestern-southeastern oriented extension follows and results in continental break-up and oceanic spreading. Our results suggest a segmentation of the Central Mozambique margin with oceanisation first occurring in the Angoche segment. The formation of the first oceanic crust in the Beira segment followed, likely delayed by the formation and failure of the northern Beira High rift. Highlights: Margin is characterised by intense but localised volcanism including SDR formation. Polyphase rifting recorded by Beira High pre-rift sediments. Formation and failure of a rift in the Zambezi Delta Depression likely delayed break-up in. Beira segment. OCTs formed by lower crust exhumation in Angoche and southern Beira High margins.